Ritratto di un tomista : profilo storico-filosofico di Réginald Garrigou-Lagrange - Bracchi, Marco (Sapientia, 2021)
Réginald Garrigou-Lagrange O.P. (1877-1964), professor at the Angelicum in Rome, was one of the most renowned Thomists of the first half of the 20th century. The article aims to trace the biographical profile of Garrigou-Lagrange not only through the salient historical data, difficult to find in other biographies, but also thanks to the comparison with some philosophical currents with which the theologian was confronted. After the presentation of the family origins and the native cultural climate of the thinker, the stages of his training prior to entering religion were retraced. Of particular consideration is the event that marks a turning point in Garrigou-Lagrange’s life, the “second conversion” that will lead him to enter the Dominican Order. In retracing the excursus of his philosophical-theological training, the comparison with modern philosophies – Materialism, Agnosticism, Philosophies of life and of becoming – is profoundly linked to the personal life and the modus cogitandi of our Thomist. Without neglecting his role as spiritual director and his pastoral activity, as well as his irrefutable theological contribution in the dogmatic field, the study finds its epilogue with the memory of the last years that will lead to the death of Garrigou-Lagrange.